A Bibliometric Analysis of Impulsive Buying Research in Business and Management: Trends, Collaboration, and Future Research Directions (2020–2026) - Yunita Kartika Sari; Bambang Widjanarko (Sean Institute, 2026)
Impulsive buying is the most topic in consumer behaviour and marketing study due to digital commerce, social media, and mobile technologies development. Unfortunately, a comprehensive overview of collaboration patterns, intellectual structure, and emerging research themes are still limited. This study aims to map the development of impulsive buying research within the Business, Management and Accounting discipline using a bibliometric approach. The data is retrieved from the Scopus database using query TITLE-ABS-KEY(